Applications of transcriptomics in support of drug development for osteoarthritis. Issue 4 (December 2021) - Kaplon, Hélène; Luo, Yufei; De Ceuninck, Frédéric; Lalande, Agnès; Courtade-Gaiani, Sophie; Laigle, Laurence; Moingeon, Philippe
Abstract: Objective: Understanding the heterogeneity and pathophysiology of osteoarthritis (OA) is critical to support the development of tailored disease-modifying treatments. To this aim, transcriptomics tools are highly relevant to delineate dysregulated molecular pathways and identify new therapeutic targets. Methods: We review the methodology and outcomes of transcriptomics studies conducted in OA, based on a comprehensive literature search of the PubMed and Google Scholar databases using the terms "osteoarthritis", "OA", "knee OA", "hip OA", "genes", "RNA-seq", "microarray", "transcriptomic" and "PCR" as key words. Beyond target-focused RT-qPCR, more comprehensive techniques include microarrays, RNA sequencing (RNA-seq) and single cell RNA-seq analyses. Results: The standardization of those methods to ensure the quality of both RNA extraction and sequencing is critical to get meaningful insights. Transcriptomics studies have been conducted in various tissues involved in the pathogenesis of OA, including articular cartilage, subchondral bone and synovium, as well as in the blood of patients. Molecular pathways dysregulated in OA relate to cartilage degradation, matrix and bone remodeling, neurogenic pain, inflammation, apoptosis and angiogenesis. This knowledge has direct application to patient stratification and further, to the identification of candidate therapeutic targets and biomarkers intended to monitor OA progression. Conclusion: In light of its high-throughput capabilities and ability to provide comprehensive information on major biological processes, transcriptomics represents a powerful method to support the development of new disease-modifying drugs in OA.